Koppa Archaeological Research Project (KARP): Exclusive Iron Age landscapes in the Western Ghats, India. (March 2019) - Arjun, R.; Korisettar, Ravi; Deo, Sushama; Mushrif-Tripathy, Veena; Naik, Satish; Jadhav, Shreekant; Mallinathpur, Yogesh
Abstract: Koppa Archaeological Research Project (KARP) conducted systematic transect surveys and excavations in the Coorg plateau at the upper reaches of river Kaveri in the Western Ghats, Karnataka. The archaeological record of the study area is exclusively an Iron Age landscape, as we did not find any other prehistoric or early historic sites. We focused on studying thirty-nine Iron Age (1200 BCE–300 BCE) sites of two categories, habitation and megaliths, and we present here our preliminary observations addressing to site findings, their landscapes and settlement patterns. We then consider the geographical and climatic implications for understanding the formation of their economy and politics. We argue that sites in the Western Ghats did not differ significantly from the temporal and cultural material typologies of contemporary Iron Age sites in the semi-arid or savannah conditions of Deccan plateau. Yet the adaption of Iron Age communities to Western Ghats climate which is characterized by high rainfall, lush tropical forests, fallow lands and diverse faunal ecology should have had distinct implications for the development of their economy and politics.